Boekhandel Tan Khoen Swie, press movement, and Javanese public sphere in the colonial age 1915-1950 - Ratya Anindita; I Wayan Suyadnya; Ary Budianto; Megasari Noer Fatanti (Masyarakat, Kebudayaan dan Politik, 2017)
The research attenots to analysis the historical genealogy and press movement and Javanese public sphere in the colonial age, 1915-1950. By focusing the site of Boekhandel Tan Khoen Swie (TKS) in Kediri - East Java during the colonial period, this research is specifically to explore the roles of TKS and Tan Khoen Swie’s ideas (as a person) in the press movement in East Java over 35 years. The research used qualitative research with historical-discourse perspectives. It combines the archeology/genealogy methods proposed by Michel Foucault, historical and archives study. Through a historical archive investigation, both of material and ego documents, the study mapped on how the production of the public sphere in colonial age happened. The result of this study shows that the works and ideas published by through Boekhandel Tan Khoen Swie (TKS) are full meaning of spiritual and culture values. TKS has encouraged the transformation of Javanese values to the wider community. We argue that the idea and efforts of the public sphere in Javanese community during the colonial era, especially through it controversial publications. As an individual, Tan Khoen Swie established himself as the cosmopolitan elite in the fight against the colonialism. In other words, the study is success to showed the importance roles of Tan Khoen Swie inspiring the emergence of press movement in East Java and it also supports for creating the alternative public sphere for Javanese.